Comparison of otological and audiological outcome of type-I tympanoplasty using composite tragal perichondrium and temporalis fascia as graft - Sharma, Nitin; Sharma, Pritosh; Sharma, Prateek; Gourav, Kumar; Goyal, V. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The most frequently used technique for the repair of TM perforation is underlay grafting of temporalis fascia in normally ventilated middle ears. In advanced middle ear pathology, large perforations, atelectatic drum or retraction pockets, temporalis facia may cause higher failure rates. In such cases, a more rigid grafting material such as cartilage is preferred because of its increased stability and resistance to middle ear pressure even in cases with chronic eustachian tube dysfunction. Methods: This is a prospective randomized study design on comparison of temporalis fascia and cartilage as graft in patients of CSOM with subtotal perforation. 80 patients, divided randomly into two groups with equal patients, with tragal cartilage (group 1) and temporalis fascia (group 2) as graft. Follow up done at post-operative 3rd week and 3rd month for graft acceptance as well as graft health. Audiometric evaluation was conducted at 3rd month. The data obtained was subjected to appropriate statistical analysis using SPSS version 20. Results: Graft uptake rate in group1 and 2 was 93.75% and 90%. The mean AB gap improved in group1from 36.38±6.10 dB to 18.13±5.84 dB. Similarly in group 2 it improved from 28.73±5.82 dB to 15.23±8.14 dB; showed statistically highly significance in both groups (p<0.001). Conclusions: Composite tragal perichondrium graft delivers an excellent audiologic outcome comparable to temporalis fascia graft specially where medialization of graft is expected. It gives ENT surgeons a reliable armamentarium in tympanoplasties for subtotal perforation.